2013
DOI: 10.1089/lrb.2013.0014
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Proteins Are Represented in Tissue Fluid/Lymph from Soft Tissues of Normal Human Legs at Concentrations Different from Serum

Abstract: Background: The mobile intercellular fluid flowing to and in the lymphatics contains filtered plasma products and substances synthesized and excreted by tissue cells. Among them are signaling proteins such as cytokines, chemokines, enzymes, and growth factors. They act locally in autocrine and paracrine systems regulating cell metabolism, proliferation, and formation of the ground matrix. They play an immunoregulatory role in infections, wound healing, and tumor cell growth. Methods and Results: In this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…This could be accounted for by a lower level of cytokines responsible for the proliferation of KC in serum than in TF/L. 9 We also observed that there was a significant increase in the percentage of KC expressing the PCNA and Ki67 proliferation markers after culture in the lymphedema TF/L compared to those cultured in TF/L from healthy controls, 20% serum or RPMI (Fig. 3b,c).…”
Section: Keratinocyte Mitotic Indexmentioning
confidence: 63%
See 2 more Smart Citations
“…This could be accounted for by a lower level of cytokines responsible for the proliferation of KC in serum than in TF/L. 9 We also observed that there was a significant increase in the percentage of KC expressing the PCNA and Ki67 proliferation markers after culture in the lymphedema TF/L compared to those cultured in TF/L from healthy controls, 20% serum or RPMI (Fig. 3b,c).…”
Section: Keratinocyte Mitotic Indexmentioning
confidence: 63%
“…Epidermis, in particular its basal layer, remains in a direct contact with mobile tissue fluid generated by the capillary plasma filtration process. This fluid contains humoral factors, which can have stimulatory or repressive regulatory properties on KC and fibroblasts . The composition of the TF/L differs from that of plasma, although it is the product of diffusion and filtration of plasma components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We now know that a broad array of cytokines, proteins, growth factors are contained within lymphatic fluid, which play an important role in metabolism, proliferation, as well as an immunoregulatory role [54]. When comparing with serum concentrations, Zaleska  et al.…”
Section: Lymph Composition In Lymphatic Functionmentioning
confidence: 99%
“…In addition, previous studies have shown that the expression of IL-6 is increased in both primary and surgical models of lymphedema (20,28). Finally, a recent study has shown that the concentration of IL-6 is higher in lymph fluid as compared with subcutaneous fat, suggesting that the lymphatics play a role in transport or clearance of inflammatory cytokines (38).…”
mentioning
confidence: 98%